2022
DOI: 10.13075/ijomeh.1896.01882
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a source of information on carbon monoxide poisoning: a content-quality analysis.

Abstract: Objectives:The variety of clinical presentation on the topic of carbon monoxide (CO) intoxication ranges from slight headache to coma or death. YouTube allows patients to search not only for entertainment but also medical advice. Therefore, the aim of this study was to evaluate the content and quality of YouTube videos concerning CO poisoning as a source of knowledge for non-medical audience. Material and Methods: On the December 8, 2020 a YouTube search was conducted for the following phrases: "carbon monoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…More and more people are turning to YouTube for health information, but the overall quality of these videos is poor. Krakowiak et al [ 31 ] found that the mean DISCERN/JAMA score was 28.1 ± 7.9 and 1.1 ± 0.7, respectively, and more importantly, the videos providing misleading information had a higher like ratio. This worrying state of video platforms may easily lead to patient misunderstandings and prevent them from correct choices and timely treatment, especially for acute diseases.…”
Section: Discussionmentioning
confidence: 99%
“…More and more people are turning to YouTube for health information, but the overall quality of these videos is poor. Krakowiak et al [ 31 ] found that the mean DISCERN/JAMA score was 28.1 ± 7.9 and 1.1 ± 0.7, respectively, and more importantly, the videos providing misleading information had a higher like ratio. This worrying state of video platforms may easily lead to patient misunderstandings and prevent them from correct choices and timely treatment, especially for acute diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 11,12,14 The Global Quality Scale (GQS) was used to evaluate the educational content quality of the videos (Table 1). 6,12–17 We used the modified DISCERN score to analyze the reliability and quality of the videos (Table 1). 12,13,15,17,18 …”
Section: Methodsmentioning
confidence: 99%
“…12 For video reliability, 4-criterion Journal of American Medical Association (JAMA) benchmarks criteria were used (described in Table 1). 11,12,14 The Global Quality Scale (GQS) was used to evaluate the educational content quality of the videos (Table 1). 6,[12][13][14][15][16][17] We used the modified DISCERN score to analyze the reliability and quality of the videos (Table 1).…”
Section: Video Reliability and Content Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In almost 86% of cases, YT videos on meningiomas did not include a definition, and only 12 videos informed the viewer when to seek medical attention. Medical conditions during childbearing represent a topic that is often omitted; in this case, only three YT videos discussed meningiomas in pregnancy, compared to four for CO intoxication videos [ 31 ] and one for arteriovenous malformation [ 10 ]. YT is more frequently used by medical students for learning purposes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%